Hospital Clostridium difficile Infection Rates and Prediction of Length of Stay in Patients Without C. difficile Infection. (9th February 2016) - Miller, Aaron C.; Polgreen, Linnea A.; Cavanaugh, Joseph E.; Polgreen, Philip M.
Abstract : BACKGROUND: Inpatient length of stay (LOS) has been used as a measure of hospital quality and efficiency. Patients with Clostridium difficile infections (CDI) have longer LOS. OBJECTIVE: To describe the relationship between hospital CDI incidence and the LOS of patients without CDI. DESIGN: Retrospective cohort analysis. METHODS: We predicted average LOS for patients without CDI at both the hospital and patient level using hospital CDI incidence. We also controlled for hospital characteristics (eg, bed size) and patient characteristics (eg, comorbidities, age). SETTING: Healthcare Cost and Utilization Project Nationwide Inpatient Sample, 2009–2011. PATIENTS: The Nationwide Inpatient Sample includes patients from a 20% sample of all nonfederal US hospitals. RESULTS: Inpatient LOS was significantly longer ( P <.001) at hospitals with greater CDI incidence at both the hospital and individual level. At a hospital level, a percentage point increase in the CDI incidence rate was associated with more than an additional day's stay (between 1.19 and 1.61 days). At the individual level, controlling for all observable variables, a percentage point increase in the CDI incidence rate at their hospital was also associated with longer LOS (between 0.6 and 1.05 additional days). Hospital CDI incidence had a larger impact on LOS than many other commonly used predictors of LOS. CONCLUSION: CDI rates are a predictor of LOS in patients without CDI at an individual and institutional level. CDI rates are easy to measure and report and thus may provide an important marker for hospital efficiency and/or quality. Infect. Control Hosp. Epidemiol. 2016;37(4):404–410